PENGARUH KOMPENSASI DAN PERSEPSI KEADILAN TERHADAP KINERJA PEGAWAI DENGAN MEDIASI KOMITMEN ORGANISASIONAL (Studi Pada RSUD RAA Soewondo Kabupaten Pati) - Nita Enggar Sari, 1352020057 (Jurnal Mahasiswa Pasca Sarjana, 2015)
The purpose of this research are to examine the influence of compensation and perception of fairness to the performance by organizational commitment as a intervening variabelin the RSUD RAA Soewondo Pati Regency. This research uses multiple regression linear that uses data collection techniques with questionnaires to measure using a Likert scale of 7 (seven) alternative answers. Object of this research is the employees at RSUD RAA Soewondo Pati regency. Number of samples in this research were 175 respondents that uses purposive sampling as sampling technique. Survey results revealed that compensation and perception of fairness have positive and significant influence toward organizational commitment in the RSUD RAA Soewondo Pati Regency. compensation and perception of fairness have positive and significant influence toward employees performance in the RSUD RAA Soewondo Pati Regency. Organizational commitment has positive and significant influence toward employees performance in the RSUD RAA Soewondo Pati Regency. Organizational commitment mediates the relationship between compensation and perception of fairness toward employees performance in the RSUD RAA Soewondo Pati Regency. Keywords: Compensation, Perception of Fairness, Organizational Commitment, Performance